What is the future of work? A science mapping analysis. Issue 6 (December 2020) - Santana, Monica; Cobo, Manuel J.
Abstract: This article aims to systematise and provide a structure for research into the Future of Work (FoW). We used SciMAT to conduct a science mapping analysis based on co-word bibliographic networks. The Web of Science (WoS) database was used for article retrieval, and a total of 2, 286 documents were identified from 1959 to 2019. Our results are counterintuitive, as concerns over satisfaction, leadership values or corporate social responsibility (CSR) appear alongside traditional human resource management (HRM) themes, such as organisational commitment or careers, as well as more current FoW themes, such as the impact of technological change on employment, wage inequality, vulnerable workers, telework or talent management. In addition, we offer a classification of the most prolific FoW research themes and challenges into technological, social, economic and political categories.